Ischemia during exercise stress testing, an indication of coronary vasomotor dysfunction? - Diantha J.M. Schipaanboord; Tijn P.J. Jansen; Luuk Scherpenhuijzen; Caïa Crooijmans; Aukelien C. Dimitriu-Leen; Pim van der Harst; Tim P. van de Hoef; René van Es; Hester M. den Ruijter; Peter Damman; N. Charlotte Onland-Moret; Suzette E. Elias-Smale (International Journal of Cardiology: Heart & Vasculature)
Background: Recently it has been suggested that coronary microvascular dysfunction (CMD) may explain the high false-positive rate of exercise electrocardiographic stress testing (EST). However, patients with angina but non-obstructive coronary artery disease (ANOCA) present with a broader spectrum of coronary vasomotor dysfunction (CVDys), namely coronary artery spasm (CAS), CMD or a combination of both. We aim to investigate the diagnostic value of EST for the entire CVDys spectrum. Methods: We included patients who underwent coronary function testing (CFT) in the Radboud University Medical Center. For each patient we requested the most recent EST report. ESTs were denoted as positive for ischemia if clinically significant ST-segment depression was detected. We calculated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) with 95% confidence intervals for the diagnosis of CVDys and its endotypes. Results: Of the 105 included patients (87 % women, mean age 57 (±8) years), 22 (21 %) had ischemia during EST. CVDys was diagnosed in 94 patients (90 %), of whom 58 patients had an isolated endotype (CAS: n = 51, CMD: n = 7) and 36 patients had CAS and CMD. Ischemia during EST yielded a high specificity and PPV for CVDys (specificity: 100 % (71.5–100 %), PPV: 100 % (84.6–100 %)), which remained reasonably similar for CAS (specificity: 94.4 % (72.7–99.9 %), PPV: 95.5 % (77.2–99.9 %)), but was lower for CMD (specificity: 85.5 % (74.2–93.1 %), PPV: 59.1 % (36.4–79.3 %)). Conclusions: Ischemia during EST is highly specific for CVDys in general and can be an indicator for CAS and to a lesser extent for CMD in patients with ANOCA.